SLOW RELEASE MELATONINE IN METABOLIC SYNDROME SYMPTHOMATICS CORRECTION - V. O. Smirnova; I. N. Barykina; A. S. Salasyuk; V. Yu. Khripaeva; R. V. Palashkin; S. V. Nedogoda (Российский кардиологический журнал, 2016)
Aim. To compare effectiveness of metformin monotherapy (Mf) and combination of metformin with slow release melatonine (MfM) from the perspective of correction of anthropometric, hemodynamical parameters, premature vascular ageing and somnological status in patients with metabolic syndrome (MS).Material and methods. An open label prospective comparative study conducted, in 3 parallel groups: 238 MS patients (IDF, 2005) having, at the moment of prescreening, sleep disorders (less than 19 points in Questionnaire of self sleep evaluation), were randomized to 3 groups. During 12 weeks all patients underwent life style correction that included regimen of meal intake, normalization of “sleepwakefulness” rhythm, physical activity. In addition to this, first group patients (n=80) received Mf, and second (n=78) — combination MfM (Circadin 2 mg). Controls (n=80) were patients without pharmaceutical interventions. Groups were comparable by the baseline clinical and demographic characteristics. Sleep quality, anthropometric and metabolic parameters, adipocytokine level and vascular elasticity parameters were assessed at baseline and in 12 weeks after treatment.Results. The results of the study performed have proved the feasibility of melatonine slow release addition to standard MS therapy in circadian disorders (CD). MfM no only normalizes the rhythm “sleep-wakefulness”, but also retards vascular ageing, has positive profile of cardiovasular and metabolic effects, acting on insulin resistance as trigger of MS development. Serious adverse events were not marked during the study. Conclusion. Combination therapy by MfM is more effective than monotherapy by Mf in correction of body overweight, carbohydrate and lipid metabolism disorders in MS with CD.